Contract adjustment under uncertainty - Helge Holden; Lars Holden; Steinar Holden (Center for Economic Studies and ifo Institute (CESifo), 2005)
Consider a contract over trade in continuous time between two players, according to which one player makes a payment to the other, in exchange for an exogenous service. At each point in time, either player may unilaterally require an adjustment of the contract payment, involving adjustment costs for both players. Players? payoffs from trade under the contract, as well as from trade under an adjusted contract, are exogenous and stochastic. We consider players? choice of whether and when to adjust the contract payment. It is argued that the optimal strategy for each player is to adjust the contract whenever the contract payment relative to the outcome of an adjustment passes a certain threshold, depending among other things of the adjustment costs. There is strategic substitutability in the choice of thresholds, so that if one player becomes more aggressive by choosing a threshold closer to unity, the other player becomes more passive. If players may invest in order to reduce the adjustment costs, there will be over-investment compared to the welfare maximizing levels.
Keywords: C72; E31; C78; C73; 330; Vertragstheorie; Betriebliche Preispolitik; Verhandlungstheorie; Nichtkooperatives Spiel; Anpassung; Theorie